Conceptual mapping of geography textbook content on the example of the desert biome - Petr Trahorsch; Jan Daniel Bláha; Kristýna Ryčlová (European Journal of Geography)
The aim of this study is to identify the key terms used by textbook authors when presenting desert biomes and, subsequently, to visualise the relationships between them using a conceptual map. To achieve this objective, we assessed geography textbooks using conceptual maps, which can be used to conceptualise this topic. The method used is innovative in textbook research and can be used to present results in a visual form with added value. A total of eleven university students created conceptual maps for each of the five analysed textbooks, and this was followed by a synthesis and comparison of the created maps. The effectiveness and clarity of the analysed content is one of the advantages of this visual form of analysis. The data were analysed qualitatively and quantitatively. The results show that the presentation of desert biomes in the textbooks we analysed is somewhat superficial, as the authors do not strive to interconnect concepts from different areas, and their conceptual maps lack higher hierarchy levels. Therefore, textbook authors should opt for a different conceptual approach to explanatory texts instead of the traditional coverage of the individual components of geographical environments.